2018
DOI: 10.1016/j.beth.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Job Stress and Satisfaction in Urban Schools: Disentangling Individual-, Classroom-, and Organizational-Level Influences

Abstract: Schools remain among the most frequent providers of children's mental health services, particularly in low-income urban settings. Several decades of research have focused on training teachers to implement evidence-based interventions for minimizing disruptive behavior. Studies consistently demonstrate robust improvements in student behavior and learning; however, the impact on teachers' work-related stress or satisfaction is not well understood. Six urban, high-poverty elementary schools were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 59 publications
3
91
0
11
Order By: Relevance
“…Some teachers reported difficulties deploying it effectively within their classrooms if teaching assistants did not agree or follow the same strategies (Ford et al ., ). A consistent whole‐school approach to TCM, that involves teaching and playground assistants as well as teachers, may be more effective, particularly as a recent trial of two evidence‐based approaches to children's behavioural management suggested that organizational level factors were the strongest predictors of teachers’ stress and job satisfaction (Ouellette et al ., ). It is intuitively plausible that if behavioural management strategies perceived to be helpful and effective were conflicting with the wider school approach, access to TCM training might undermine rather than improve teacher well‐being.…”
Section: Discussionmentioning
confidence: 97%
“…Some teachers reported difficulties deploying it effectively within their classrooms if teaching assistants did not agree or follow the same strategies (Ford et al ., ). A consistent whole‐school approach to TCM, that involves teaching and playground assistants as well as teachers, may be more effective, particularly as a recent trial of two evidence‐based approaches to children's behavioural management suggested that organizational level factors were the strongest predictors of teachers’ stress and job satisfaction (Ouellette et al ., ). It is intuitively plausible that if behavioural management strategies perceived to be helpful and effective were conflicting with the wider school approach, access to TCM training might undermine rather than improve teacher well‐being.…”
Section: Discussionmentioning
confidence: 97%
“…Ross et al (2012) also found that teachers in elementary schools implementing Positive Behavioral Interventions and Supports with high fidelity reported significantly lower levels of burnout than teachers in low fidelity schools. These results have not always been consistent however, as Ouellette et al (2018) found no association between elementary school teachers’ adherence to four classroom interventions to reduce disruptive behaviors and promote learning, and teacher stress, a construct highly correlated with emotional exhaustion.…”
mentioning
confidence: 86%
“…While all teacher experience stressors, teachers in urban schools, as opposed to their suburban counterparts, may more acutely experience such challenges, given that students in urban environments are more likely to experience social–emotional difficulties (Atkins, Graczyk, Frazier, & Adil, ; Balfanz, Herzog, & Mac Iver, ). In turn, teachers in urban schools, who disproportionately serve low‐income and minority students, encounter notably higher levels of stress than teachers in other schools (Ouellette et al, ; Shernoff, Mehta, Atkins, Torf, & Spencer, ). Faced with higher levels of stress and oftentimes without adequate support to meet their students’ needs, urban teachers increasingly experience burnout, a process of repeated emotional exhaustion, depersonalization, and feelings of a lack of personal accomplishment, which leads them to leave the teaching profession at alarming rates (Fantuzzo et al, ; Yang, Ge, Hu, Chi, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to identify ways that stress can be reduced for teachers so that they can function more effectively and be less likely to leave the profession (Ouellette et al, ). Thus, the current study was designed to explore urban teachers’ thoughts and feelings in response to challenging classroom situations, the prevalence of these thoughts and feelings, and their help‐seeking attitudes in coping with emotional distress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation